i-MoBE system for educators in higher learning institution - Abdullah, Rusli; Ali, Abdifatah Farah (UTM Academic Leadership (UTMLead), Universiti Teknologi Malaysia, 2016)
Outcome-based Education (OBE) right now is very important to the academician, especially in Higher learning Institutions (HLI) in ensuring the student will get the benefits in Teaching and Learning (T&L) of their study. In this context, there is a lacking of the intelligent mobile OBE system model in helping the academician to use in OBE management for T&L environment. Since that, the implementation of the OBE as a system model for mobile application called as i-MoBE which main objectives is to offer the academician and easy and straightforward access to general information about their courses in T&L intelligently. So that it’s easy to monitor the OBE of student achievement based on Cognitive, Psychomotor and Affective (CPA). Therefore, in this research we will be highlighting a system model of intelligent OBE for academician in HLI. The proposed model will be covering the conceptual design and its interaction as well as the system configuration in supporting the academician to use it in their T&L towards effectiveness and its efficiency.